Maataloustuotteiden tuotantokustannukset viljelmämalleilla - Ala-Mantila, Ossi (fi, 1998)
The Agricultural Economics Research Institute has calculated the production costs of the major agricultural products since the 1970s. The calculations are used to examine the development of production costs, and they are based on the farm models. These farm models are constructed partly on the basis of information compiled from bookeeping farms and on the basis of various standards and recommendations. The models describe a situation where a farm has specialised in a production of one product. The farm models represent the conditions in Southern Finland and a level of agriculture more efficient than average. Therefore, the production costs calculated on the basis of these models do not descride the average production costs of farm products in Finland. The production methods and yields of the farm models have now been revised to correspond to the current situations. The calculations consist of the production of milk, beef, pork, piglets, eggs, bread grain, feed grain, oil plants and sugar beets. The calculations are made for each product produced on farms of different sizes and so they show the effect of the farm size on the production costs. The total number of models presented in this report is 50. The cost structures of the models are based on the production costs determined at the price and cost level of the year 1996.
Abstract
Keywords: tuotantokustannukset; tilamallit; maito; naudanliha; sianliha; porsaat; kananmunat; vilja; öljykasvit; sokerijuurikas; production costs; farm models; milk; beef; pork; piglets; eggs; grain; oil plants; sugar beets